Application of the Principles of Green Chemistry for the Development of a New and Sensitive Method for Analysis of Ertapenem Sodium by Capillary Electrophoresis - Tahisa Marcela Pedroso; Ann Van Schepdael; Hérida Regina Nunes Salgado (International Journal of Analytical Chemistry)
An innovative method is validated for the analysis of ertapenem sodium by capillary electrophoresis using potassium phosphate buffer 10 mM pH 7 and 15 kV voltage, in the concentration range of 70 to 120 μg mL−1. Ertapenem had a migration time of 3.15 minutes and the linearity curve was y = 2281.7 x - 24495 with a R2 = 0.9994. Thus, we propose a routine analysis method that meets the principles of green analytical chemistry for the routine analysis of ertapenem sodium by capillary electrophoresis.